Ensuring the growth of the country’s economy - L. A. Akhmetov; M. A. Bulavina (Путеводитель предпринимателя, 2024)
The article examines and analyzes the problems and issues of the dynamics of the country’s economy (GDP) under the influence of external and internal factors and conditions in the second half of the year and in general for 2023. The dynamics of inflation and the value of the key rate of the Central Bank of the Russian Federation, the volatility of the Russian ruble, the real effectiveness of the ruble exchange rate, which reveals the dynamics of exchange rates through the average value of the exchange rates of trading partners. Provides a short list of sanctions imposed in the second half of 2023 by unfriendly countries against Russia, effective measures taken by government agencies and business to ensure the successful functioning of the economy countries in the context of geopolitical tensions and sanctions restrictions.